Study on pressure sensitivity of tight sandstone and its influence on reservoir characteristics. Issue 22 (17th November 2018) - Gu, Yang; Ding, Wenlong; Yin, Min; Liu, Jingshou; Xiao, Zikang; Jiao, Baocheng; Shen, Haoran
ABSTRACT: The rocks with low permeability have a strong sensitivity to pressure. By changing the size of confining pressure, we can realize the effective stress change of rocks and calculate the permeability change under different effective stress to evaluate the stress sensitivity of the reservoir. We analyzed the factors affecting the stress sensitivity of tight sandstone reservoir, including material composition, fracture development, and pore structure of rock. The results show that the stress sensitivity of microfractured core is very weak, and the permeability change rate is less than 20%. The sensitivity curve is divided into two stages: the permeability decline rate in the first stage is more than 30%, mainly due to the pseudoplastic deformation of the fracture under compression. In the second stage, the decrease of permeability is less than 30%. At this stage, the elastic deformation mainly depends on the compression of the rock skeleton particles, and the net stress of the actual reservoir is mostly at this stage. Therefore, the application of the second stage to evaluate the stress sensitivity of reservoirs is more practical, and the stress sensitivity of microfracture cores is higher than that of matrix cores. Through the analysis of pressure-sensitive mechanism and experimental data, it is concluded that the main controlling factors affecting rock stress sensitivity are fracture development and pore structure of rock, while rock material composition is a relatively minor factor.